Conversion of Memory in Architecture and Culture of İstiklal Street Between 2005- 2019 - Sav, Sedef; KARABETÇA, ALİYE RAHŞAN (My University, 2019)
Beyoğlu which was called “Pera”, meaning “other”, “other side, “opposite side”, by Genoese and Venetians, and plays an important role in the existence of İstanbul, had faced different transformations in different periods. The main route of this district called as İstiklal Street (Grand Rue de Pera) had been affected by this transformation in cultural and architectural aspects. The rapid progress of this transformation, especially between the years 2005-2019, brought about a negative conversion. This conversion had led to a serious architectural and memory destruction of the Street and this situation is still continuing. The fact that this damage/transformation cannot be sustained/avoided in terms of cultural memory and belonging prevents future generations from establishing a bond with their past. Therefore, the purpose of this study is to underline the reasons for triggering this process instead of preventing the original values of İstiklal Street which is an important data for user profile and memory. Within this scope, the paper draws attention to negativity by emphasizing the main reasons for changing the cultural structure, demography, and architecture of İstiklal Street. In this paper, a comparison was made between street images of 2005 and 2019 to ascertain how the architectural conversions were made based on façades and functions. The changes that happened between 2005- 2019 over the existing, destructed and new buildings were discussed. The relationship between functional changes in buildings, design approaches for new constructions and user profiles were evaluated within the scope of memory and transformation. In addition, a profound literature review was conducted and it was investigated whether there were connections between the previous transformations of the street and the dates mentioned in the paper. Between 1942 and 1964, the migration policies applied to non-Muslims originating from the inclusion of capital tax, the establishment of the state of Israel, the events of September 6-7 and the Cyprus problems led to a major transformation of the street in cultural terms. This also effected the user profile and function of the abandoned buildings. Besides, while the entire Istanbul was transformed by the demolitions of 1957-58 and 1986-88, the Beyoğlu district was significantly affected by this change both in positive and negative ways. With the closure of İstiklal Street to the traffic and re-start of the tram service, architecture and culture on the street started to revive (inal, 2014). Nowadays, this transformation is made in different ways and it is aimed to change the cultural memory, so the architecture of the street has changed in this direction. This study provides information on how the architectural and cultural changes can continue in the future that the street has undergone so far.
Keywords: İstiklal Street; Memory; Conversion; Transformation; İstiklal Caddesi; Bellek; Dönüşüm; Transformasyon